Multiple sites of thrombosis without thrombocytopenia after a second dose of Pfizer-BioNTech COVID-19 vaccine. (14th September 2022) - Scendoni, Roberto; Petrelli, Cristina; Giustozzi, Mauro; Logullo, Francesco O
In the current international scientific panorama, rare cases of venous thrombotic complications following mRNA vaccine administration have been reported, consisting mainly of cerebral sinus thromboses and acute venous thromboembolism. The present paper describes the case of a 75-year-old woman in good health who developed cerebral venous thrombosis, deep venous thrombosis, and bilateral pulmonary emboli after receiving a second dose of Pfizer-BioNTech COVID-19 vaccine. A series of laboratory tests performed during hospitalization yielded interesting results, allowing us to exclude thrombophilic risk factors and to certify the absence of thrombocytopenia in the patient. Although COVID-19 vaccination is the most important tool in stopping the pandemic, pharmacovigilance is crucial for detecting potential multisystem thrombotic events, even for mRNA vaccines.